2017
DOI: 10.1080/10520295.2017.1339912
|View full text |Cite
|
Sign up to set email alerts
|

Study of response of Swiss Webster mice to light subunit of mushroom tyrosinase

Abstract: The light subunit of mushroom, Agaricus bisporus, tyrosinase (LSMT), has been identified as an extrinsic component of the enzyme. Its function is unknown, but it can cross an epithelial cell layer, which suggests that it can be absorbed by the intestine. A similar capability has been demonstrated for the HA-33 component of the progenitor toxin from Clostridium botulinum, which is the closest structural homolog of LSMT. Unlike HA-33, LSMT appears to be non-immunogenic as shown by preliminary tests in Swiss Webs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A preliminary immunogenicity test in Swiss Webster mice suggested that Abmb does not evoke a response of the immune system [20]. Further toxicity and immunogenicity tests with the inbreed and outbreed mice showed that Abmb was safe after prolonged administration at an elevated dose [64,65]. These results strengthen the safety profile of Abmb.…”
Section: Abmbmentioning
confidence: 66%
“…A preliminary immunogenicity test in Swiss Webster mice suggested that Abmb does not evoke a response of the immune system [20]. Further toxicity and immunogenicity tests with the inbreed and outbreed mice showed that Abmb was safe after prolonged administration at an elevated dose [64,65]. These results strengthen the safety profile of Abmb.…”
Section: Abmbmentioning
confidence: 66%
“…Production and Purification of rLSMT rLSMT was prepared according to the previous report. 9) Briefly, E. coli BL21 (DE3)-rLSMT was grown at 37°C in LB medium containing 100 µg/mL ampicillin for 10-12 h (overnight). Protein expression was induced by the addition of IPTG to a final concentration of 0.05 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Permeability Study The permeability study was performed by the non-everted gut sac method as previously reported. 9) First, a Wistar rat was acclimatized without food but with free access to drink water for 12 h prior to sacrificing it in a CO 2 chamber (3-4 min at 30% CO 2 ). The jejunum was collected and immediately divided into three of five-centimeter segments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, tyrosinase from common white button mushrooms Agaricus bisporus ( TyrAB ), with broad availability compared with human tyrosinase, has been used in the development of TYR–inhibitors compounds [ 25 ]. Recently, it has been described that novel functions or novel activities of some part of them, especially light subunit Orf239342, are very important in cancer proliferation inhibition [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%